The Relationship between Serum Bilirubin and Inflammatory Bowel Disease - Xiaojing Zhao; Linzhen Li; Xueting Li; Jiajia Li; Di Wang; Hongjie Zhang (Mediators of Inflammation)
The associations between serum total bilirubin (sTB) levels, inflammatory marker levels, and disease activity are not well understood in patients with inflammatory bowel disease (IBD). The present study investigated the association between sTB levels and disease activity in patients with IBD. We conducted a retrospective study with a total of 242 consecutive patients with Crohn’s disease (CD) and 211 consecutive patients with ulcerative colitis (UC). The Crohn’s Disease Activity Index (CDAI) score was used to assess disease activity in patients with CD and the Mayo score of patients with UC. 255 clinically healthy subjects comprised the control group, which come from the same geographic area as the IBD group. We retrieved the clinical and laboratory parameters of patients with IBD from the medical records. Patients with IBD displayed significantly lower sTB levels than controls. sTB levels were negatively associated with C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), fecal calprotectin (FC), and hemoglobin (Hb) levels in patients with IBD. Additionally, there was a negative association between sTB levels and the CDAI score of patients with CD. sTB levels were also negatively associated with the Mayo score of patients with UC. IBD patients had lower sTB levels when compared with controls, and there was a negative correlation between sTB levels and disease activity in patients with IBD. Increased reactive oxygen species production in IBD is likely to be responsible for increased consumption of bilirubin in patients with IBD, leading to further intestinal injury. Reducing oxidative stress may be therapeutic for these patients.